Seroprevalence of bluetongue virus infection among small ruminant in foster farm programme FPV, UPM - Abdul Malek, Azeef Izzuddin (2017)
Bluetongue disease is a notifiable disease listed by the World Organisation for Animal Health (OIE) where it can causes significant problem to the ruminant industry especially in sheep. Sheep usually develops clinical signs,however occasionally other ruminants also acquire the same clinical signs. There is lack of information related to this disease status in UPM‟s foster farm goats. In Malaysia, the last known report of this disease was in 1995 and recent outbreak was in 2009. Therefore, this experiment was designed to determine the seroprevalence of bluetongue infection among small ruminants in UPM‟s foster farms and to determine the risk factors associated with the seroprevalence of the disease. Blood samples were collected from 100 goats regardless of their age, breed and gender. The blood serum samples were used to detect the antibody towards Bluetongue virus (BTV) by ELISA. The results were negative for all samples. The zero seroprevalence of bluetongue in this study could be due to the prevention measures implemented by the Department of Veterinary Services (DVS) based on the OIE guidelines. Thus, the goats from UPM‟s foster farms are free from Bluetongue.